Amnesty International and human rights activism in postwar Britain, 1945-1977 - Buchanan, Tom 1960- (Cambridge University Press, 2020)
"In this definitive new account of the emergence of human rights activism in post-war Britain, Tom Buchanan shows how disparate individuals, organisations and causes gradually came to acquire a common identity as "human rights activists". This was a slow process whereby a coalition of activists, working on causes ranging from anti-fascism, anti-apartheid and decolonisation to civil liberties and the peace movement, began to come together under the banner of human rights. The launch of Amnesty International in 1961, and its landmark winning of the Nobel Peace Prize in 1977 provided a model and inspiration to many new activist movements in "the field of human rights", and helped to affect major changes towards public and political attitudes towards human rights issues across the globe"--
Keywords: Amnesty International -- History; Amnesty International; Geschichte 1945-1977; Human rights movements -- Great Britain -- History -- 20th century; Human rights advocacy -- Great Britain -- History -- 20th century; Nonprofit organizations -- Great Britain -- History -- 20th century; Aktivismus; Menschenrecht; Großbritannien